Vida, vida humana, vida digna - Boladeras, Margarita (Logos. Anales del Seminario de Metafísica, 2007)
Philosophers bear a special responsibility in searching a horizon of meaning that properly articulates the scientific knowledge and the moral commitments of people. To carry out this task, it is fundamental to analyze the constitutive features of life in general and of human life in particular. This article puts forward some ideas on the subject, organized around the following lines: 1) some specific changes in our concept of “life” occurred along the history, 2) the dilemmas presented by current science concerning the borders of human life, especially those relative to the processes of embryonic development, 3) the significance of the ethical principle of respect for the dignity of human life, and 4) the treatment that is given to this principle in the Spanish Constitution, as well as in the most relevant international declarations in this area.